False Opposing Fear Memories Are Produced as a Function of the Hippocampal Sector Where Glucocorticoid Receptors Are Activated - Kaouane, Nadia; Ducourneau, Eva-Gunnel; Marighetto, Aline; Segal, Menahem; Desmedt, Aline (Frontiers in Behavioral Neuroscience, 2020)
Injection of corticosterone (CORT) in the dorsal hippocampus (DH) can mimic post-traumatic stress disorder (PTSD)-related memory in mice: both maladaptive hypermnesia for a salient but irrelevant simple cue and amnesia for the traumatic context. However, accumulated evidence indicates a functional dissociation within the hippocampus such that contextual learning is primarily associated with the DH while emotional processes are more linked to the ventral hippocampus (VH). This suggests that CORT might have different effects on fear memories as a function of the hippocampal sector preferentially targeted, and the type of fear learning (contextual vs. cued) considered. We tested this hypothesis in mice using CORT infusion into the DH or VH after fear conditioning, during which a tone was either paired (predicting-tone) or unpaired (predicting-context) with the shock. We first replicate our previous results showing that intra-DH CORT infusion impairs contextual fear conditioning while inducing fear responses to the not predictive tone. Second, we show that, in contrast, intra-VH CORT infusion has opposite effects on fear memories: in the predicting-tone situation, it blocks tone fear conditioning while enhancing the fear responses to the context. In both situations, a false fear memory is formed based on an erroneous selection of the predictor of the threat. Third, these opposite effects of CORT on fear memory are both mediated by glucocorticoid receptors (GRs) activation, and reproduced by post-conditioning stress or systemic CORT injection. These findings demonstrate that false opposing fear memories can be produced depending on the hippocampal sector in which the GRs are activated.